The Americanization of the apocalypse: creating America's own Bible - Akenson, Donald H. (Oxford University Press, 2023)
""Where in the world did that come from?" is a question whose informality might obscure the fact that it is a smart query, a lot more useful than are most questions stated in academic language. In the history trade, it is one that we should ask more often, for it reminds us that no event or process or person can be analyzed purely as if it were an abstract entity. All human history needs at least two coordinates-time, of course, and place. A related, more pointed query concerning any belief, ideology, social custom, economic practice or technological innovation is, "How did that come to be here?" The "here" in the question can be any place: your home today or the senate of the Roman republic in classical times, or any place and time that is amenable to historical analysis"--